Problems on the computer literacy of educators - Dagienė, Valentina (Lietuvos matematikos rinkinys, 2002)
This paper deals with the main problem of involving information technologies in education – contents of teachers’ training courses. Three directions are presented: preparation of teachers (1), in-service teacher training (2), re-qualification of the speciality (3). The main attention should be paid to the constant in-service teachers’ training. The Standard of computer literacy for educators has been developed. It should be the main sources of all teachers’ training courses on information technology. The Standard consists of two parts: technological one and educational one. The technological part is based on ECDL Start modules. The educational part is uniqu: it requires some psychological, social, and pedagogical knowledge referring to information technology usage in education. The main attention of the paper is paid to the analysis and requirements of the educational part of the Standard of computer literacy for educators.